2018
DOI: 10.1093/jas/sky175
|View full text |Cite
|
Sign up to set email alerts
|

Genomic prediction using different estimation methodology, blending and cross-validation techniques for growth traits and visual scores in Hereford and Braford cattle

Abstract: The objective of the present study was to evaluate the accuracy and bias of direct and blended genomic predictions using different methods and cross-validation techniques for growth traits (weight and weight gains) and visual scores (conformation, precocity, muscling, and size) obtained at weaning and at yearling in Hereford and Braford breeds. Phenotypic data contained 126,290 animals belonging to the Delta G Connection genetic improvement program, and a set of 3,545 animals genotyped with the 50K chip and 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Even though RRM are routinely used in genetic evaluations of longitudinal traits in several countries (Interbull, 2018), GEBV are usually generated for the accumulated yield (e.g., Winkelman et al, 2015;Jenko et al, 2017) or for phenotypes taken at specific times (e.g., Martínez et al, 2017;Campos et al, 2018), which does not allow selecting animals for the complete curve pattern. Among the reasons why RRM are not combined with genomic information in official evaluations is the fact that selection decisions made on components of RRM may be less accurate than those based on accumulated production, which may reduce the possible gains due to the inclusion of genomics compared with genomic analyses of accumulated production (Oliveira et al, 2019b).…”
Section: An Overview Of Genomic Selectionmentioning
confidence: 99%
“…Even though RRM are routinely used in genetic evaluations of longitudinal traits in several countries (Interbull, 2018), GEBV are usually generated for the accumulated yield (e.g., Winkelman et al, 2015;Jenko et al, 2017) or for phenotypes taken at specific times (e.g., Martínez et al, 2017;Campos et al, 2018), which does not allow selecting animals for the complete curve pattern. Among the reasons why RRM are not combined with genomic information in official evaluations is the fact that selection decisions made on components of RRM may be less accurate than those based on accumulated production, which may reduce the possible gains due to the inclusion of genomics compared with genomic analyses of accumulated production (Oliveira et al, 2019b).…”
Section: An Overview Of Genomic Selectionmentioning
confidence: 99%
“…Since then, ssBLUP has dominated the application of genomic selection in animal breeding (Campos et al 2018;Zhang et al 2016). Figure 2.…”
Section: Blup Alphabetmentioning
confidence: 99%
“…Since then, ssBLUP has dominated the application of genomic selection in animal breeding (Campos et al 2018;Zhang et al 2016).…”
Section: Blup Alphabetmentioning
confidence: 99%
“…Machine learning methods (especially deep learning) have the ability to deal with complex phenotypes. Common pitfalls of applying ML methods in genomic prediction include crucial but non-trivial hyperparameter selection; determination of training, validation, and testing datasets to be used and ML methods to be applied; feature selection and dimension reduction; and dealing with overfitting and hard-to-interpret results(Crossa et al 2019; de losCampos et al 2018;Sperschneider 2019). However, a few studies have demonstrated that combining multiple ML methods(González-camacho et al 2018;Grinberg et al 2019), applying domain knowledgeLi et al 2019), and taking population structure into account(Grinberg et al 2019) can improve genomic prediction accuracy of complex phenotypes.…”
mentioning
confidence: 99%